Heat Exchangers - Castro Gómez, Laura; Manuel Velázquez Flores, Víctor; Navarrete Procopio, Miriam (IntechOpen, 2022)
The demand for energy to satisfy the basic needs and services of the population worldwide is increasing as are the economic costs associated with energy production. As such, it is essential to emphasize energy recovery systems to improve heat transfer in thermal processes. Currently, significant research efforts are being conducted to expose criteria and analysis techniques for the design of heat exchange equipment. This book discusses optimization of heat exchangers, heat transfer in novel working fluids, and the experimental and numerical analysis of heat transfer applications.